Elite boxer`s competitive performance analysis - Kolodeznikov, K. S.; Krivoshapkin, P. I.; Vasilyev, E. V. (Theory and Practice of Physical Culture, 2020)
Modern boxing sport is increasingly competitive, with the individual progress and success achievable only when the individual resource and performance is fairly tested and analyzed on a permanent basis to take a full benefit of the gifts and personality qualities critical for the competitive success and successfully master and excel the win techniques and tactics. Objective of the study was to analyze the competitive performance of an elite boxer to offer the training system improvement and correction recommendations for success in the top-ranking competitions. The study included analyses of the theoretical and practical study reports and analyses of the competitive video records of a Russian Master of Sport, a national team member. Subject to analysis were the total punches classified into the body/ head punches, defense/ attack actions, and errors per round, match and tournament on the whole - for the performance analyzing purposes. We analyzed the subject`s performance in the 2015 Grand Prix Tula (4 fights, champion title), 2015 Russian Boxing Championship (3 fights, place 5), 2016 FEFT Cup (3 fights, champion title), and the 2017 Locomotive Association Cup (3 fights, champion title). The study data and analyses gave the grounds to rate the competitive performance, pace and rhythm as stable and sustainable to recommend qualification for the 69kg weight class based on the speed and performance rates. The training system was recommended being corrected as required for success in the 69kg weight class.